Q-Switched Erbium-Doped Fiber Laser Using Silver Nanoparticles Deposited Onto Side-Polished D-Shaped Fiber By Electron Beam Deposition Method - Harun, Sulaiman Wadi; Ahmad, Muhammad Taufiq; Mohd Rusdi, Muhammad Farid; Zakaria, Rozalina; Zainuddin, Nur A.M.; Ahmad, Hijaz; Abdul Latiff, Anas; Jafry, Afiq Arif Aminuddin; Arof, Hamzah (Academic Press Inc., 2019)
A stable Q-switched erbium-doped fiber laser (EDFL) is demonstrated using silver nanoparticles (AgNPs) as a passive saturable absorber. A prefabricated D-shaped silica fiber is coated with AgNPs using electron beam deposition method. Four different sizes of D-shaped fiber, which were controlled by observing the loss during the polishing process are used in this study. All four samples with losses of 1.2 dB, 2 dB, 3 dB and 3.5 dB were able to produce Q-switched pulse in 1.5-µm region, with an ability to lase at a threshold of 35.2 mW. Maximum repetition rate was recorded at 66.74 kHz for the D-shaped fiber configured with 3 dB loss, while the narrowest pulse width was obtained at 6.17 µs for 2 dB loss. All samples were also producing pulses at the maximum applicable pump power of 65.7 mW, and output power recorded at that power level are between 5.86 mW and 7.36 mW.